2007
DOI: 10.1029/2006jg000301
|View full text |Cite
|
Sign up to set email alerts
|

Robotic ecological mapping: Habitats and the search for life in the Atacama Desert

Abstract: [1] As part of the three-year 'Life in the Atacama' (LITA) project, plant and microbial abundance were mapped within three sites in the Atacama Desert, Chile, using an automated robotic rover. On-board fluorescence imaging of six biological signatures (e.g., chlorophyll, DNA, proteins) was used to assess abundance, based on a percent positive sample rating system and standardized robotic ecological transects. The percent positive rating system scored each sample based on the measured signal strength (0 for no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…SPI provided the intermediate scale in contextual imaging, between the global satellite imagery and the local‐to‐microscopic scale obtained from the fluorescence imager. This scaling continuum and nested imagery was critical in the evaluation of the presence of oases at metric to micrometric scale [ Warren‐Rhodes et al , 2007a, 2007b]. The SPI imager was also used to detect atmospheric changes, specifically the presence of morning and late afternoon fog events in the Coastal Range (as shown at Site A in Figure 1), which signaled the location of potential water accumulation on the ground and, possibly, the concentration of life.…”
Section: Rover and Science Payloadmentioning
confidence: 99%
See 1 more Smart Citation
“…SPI provided the intermediate scale in contextual imaging, between the global satellite imagery and the local‐to‐microscopic scale obtained from the fluorescence imager. This scaling continuum and nested imagery was critical in the evaluation of the presence of oases at metric to micrometric scale [ Warren‐Rhodes et al , 2007a, 2007b]. The SPI imager was also used to detect atmospheric changes, specifically the presence of morning and late afternoon fog events in the Coastal Range (as shown at Site A in Figure 1), which signaled the location of potential water accumulation on the ground and, possibly, the concentration of life.…”
Section: Rover and Science Payloadmentioning
confidence: 99%
“…An overview of the scientific and technical results of the field investigation is given in section 6. For detailed results on the geological mapping, mineralogy and biology, see Warren‐Rhodes et al [2007a, 2007b], A. Hock (Life in the Atacama: A scoring system for mapping habitability and the robotic exploration for life, submitted to Journal of Geophysical Research, 2007, hereinafter referred to as Hock et al, submitted manuscript, 2007), J. Piatek et al (Surface and subsurface composition of the Life in the Atacama field sites from rover data and orbital image analysis, submitted to Journal of Geophysical Research, 2007, hereinafter referred to as Piatek et al, submitted manuscript, 2007), and S. Weinstein et al (Application of pulsed‐excitation fluorescence imager for daylight detection of sparse life in tests in the Atacama Desert, submitted to Journal of Geophysical Research , 2007, hereinafter referred to as Weinstein et al, submitted manuscript, 2007). Finally in sections 7 and 8 we discuss and conclude on the main results of the field investigations and how the lessons learned could inform future planetary exploration and serve the exploration of extreme terrestrial environments.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to acquire fluorescence data in daylight provided the LITA team a tool to potentially map life over large regions as the rover traveled throughout each day. The results of this aspect of the field study are reported by Warren‐Rhodes et al [2007a, 2007b]. More research is required to perfect the dye probes and probe penetration for optimal use.…”
Section: Discussionmentioning
confidence: 97%
“…Hyper-arid areas can often produce significant biological crusts, sustained by the interception of fog and dew as a moisture source (Kidron, 2005;Lange et al, 2007;Shanyengana et al, 2002;Warren-Rhodes et al, 2007).…”
Section: R a I Nmentioning
confidence: 99%